Tingkat Kesejahteraan Petani Sawit di Sumatera Selatan - Nugroho, Dudy; Maad, Faizal; Budiharsono, Sugeng; Fitriani, Anna (Universitas Dr. Soetomo, 2024)
South Sumatra contribute 3,45 million CPO to Indonesia in 2022 from 1,2 million ha palmoil plantation with 18% is community plantation. The research was conducted in South Sumatra Province by taking data from a sample of 97 RSPO certified independent oil palm farmers using the Slovin method. The results of the analysis show that the welfare level of independent smallholder farmers is in good condition with an average income of IDR 2,309,075 ha/month or around US 20 per day with 3-4 ha plantation area. This data was analyzed further to obtain a subsistence exchange rate (NTS) with an average of 165, where the western cluster in Musi Rawas/North Rawas District has higher NTS value of 193, the western cluster (Lahat District) and the southern cluster (Ogan Komering Ulu /Ilir District) has the same value of 131, the eastern cluster in Musi Banyuasin District has a value of 144. The welfare of RSPO certified independent oil palm farmers in South Sumatra is influenced by the household consumption, palm oil production, FFS price, use of fertilizer and use of labor which have a simultaneous and significant influence on farmer welfare with 90% and rest 10% with other factors.